Improving care quality and preventing maltreatment in institutional care – a feasibility study with caregivers - Hermenau, Katharin; Kaltenbach, Elisa; Mkinga, Getrude; Hecker, Tobias (Frontiers in Psychology, 2015)
Institutionalized children in low-income countries often face maltreatment and inadequate caregiving. In addition to prior traumatization and other childhood adversities in the family of origin, abuse and neglect in institutional care are linked to various mental health problems. By providing a manualized training workshop for caregivers, we aimed at improving care quality and preventing maltreatment in institutional care. In Study 1, 29 participating caregivers rated feasibility and efficacy of the training immediately before, directly after, and three months following the training workshop. The results showed high demand, good feasibility, high motivation and acceptance of caregivers. They reported improvements in caregiver-child relationships, as well as in the children’s behavior. Study 2 assessed exposure to maltreatment and the mental health of 28 orphans living in one institution in which all caregivers had been trained. The children were interviewed 20 months before, one month before, and three months after the training. Children reported a decrease in physical maltreatment and assessments showed a decrease in mental health problems. Our approach seems feasible under challenging circumstances and provides first hints for its efficacy. These promising findings call for further studies testing the efficacy and sustainability of this maltreatment prevention approach.